Comparison of physical fitness and physical fitness development between deaf and hearing children - Kinsey, William Joseph (University of British Columbia, 2011)
This study attempted to determine whether or not there was a difference in the physical fitness or in the developmental change of physical fitness between deaf and hearing children. Five deaf subjects of each sex were randomly chosen from each age group (7, 9, 11, 13, and 15) from the deaf population who had no major physical or health difficulties at Jericho Hill School for the Deaf, Vancouver, B.C. Hearing subjects (10 in each age group and sex for statistical purposes) represented the population of general Canadian school-age children who did not have any major physical or health defects. Deaf subjects were administered the CAHPER Fitness-Performance Test which is composed of 6 tests (one minute speed sit-ups, shuttle run, standing broad jump, flexed arm hang, 50 yard run, and 300 yard run) and the CAHPER Physical Work Capacity Test. The results indicated no significant difference between the deaf and hearing in over all physical fitness with the exception of sit-ups and shuttle run nor in the developmental change of physical fitness. The deaf children were superior in the sit-ups but inferior in the shuttle run as compared with hearing children. Possible causes of these differences were discussed. === Education, Faculty of === Curriculum and Pedagogy (EDCP), Department of === Graduate